Growth, distribution and motivation in LDCs - Wolfgang Arnold (Intereconomics, 1979)
Economic growth leads, according to Kuznets, at first to glaring income disparities and only when a certain state of development has been reached to a levelling of incomes. Translating this thesis to the developing countries, one would have to assume that there exists a constant conflict of objectives between an equitable income distribution and increased economic growth. The author examines various alternative explanations of the personal distribution of income to answer the question how the distribution objective can be attained and what effect certain measures of distribution policy have on growth.
Keywords: 330; Distribution Policy